Development of Multiple Aortic Mycotic Aneurysms After Cardiac Catheterization. (November 2017) - Steimer, Desiree A.; Squiers, John J.; DiMaio, J. Michael; Harrington, Katherine B.
A 71-year-old male with a past medical history of coronary artery bypass surgery developed multiple, infected pseudoaneurysms of the ascending aorta and aortic root 1 year after cardiac catheterization. He underwent aortic root replacement with a 24-mm homograft. Tissue culture from operative specimens revealed invasive Aspergillus fumigatus infection. He was treated with voriconazole for 3 months. After 1 year, he had no recurrence of symptoms, pseudoaneurysm, or fungal infection.